Use of transpyloric feeds in extremely low birth weight infants at risk of severe bronchopulmonary dysplasia—a single center experience - Nagarkatti, Ahana; Sarkar, Shikha; Anuar, Amirul; Hussain, Naveed (Frontiers in Pediatrics, 2024)
Introduction: The incidence of severe BPD (sBPD), defined as needing oxygen or positive pressure at 36 weeks corrected gestational age (CGA), has remained unchanged. These infants are at risk for developing late pulmonary hypertension (LPHN) or needing surgical interventions such as Gastrostomy Tubes (GT) or Tracheostomy Tubes (TT). The finding of pepsin in the lungs of infants who were extremely low birth weight (ELBW) with sBPD has led to the speculation that gastroesophageal reflux (GER) and aspiration could contribute to their lung disease. Micro-aspiration-reducing strategies such as Transpyloric feeds (TpF) have not been well studied. Objectives: to compare ELBW infants with sBPD managed with or without TpF and determine the difference between the two groups for (i) illness severity, (ii) LPHN, (iii) need for GT, and (iv) TT; the secondary aim to study the TpF group to (i) evaluate the change in Respiratory Severity Score (RSS) before and after TpF, and (ii) evaluate the time taken to affect the change in RSS. Methods: In this retrospective study there were 229 ELBW infants with sBPD (78 in the TpF group, 151 in the non-TpF group). SPSS software was used for univariate analyses. Results: There was no difference in sex or race. TpF group had (i) a lower BW, GA, higher severity of illness (ii) higher incidence of LPHN (p<0.05), (iii) higher need for GT (p<0.001) and TT (p<0.001). In the TpF group, 60 who were on TpF for pulmonary protection from micro aspiration (lung protection group), had significantly improved RSS (p<0.05), and symptoms within 45 days in 57 out of 60 infants (95%). They improved their respiratory status by 14 days, and 80% of responders could be identified by 21 days after initiation. In the 18 that TpF was started for documented airway protection (airway protection group), there was a higher need for GT or TT. Conclusions: TpF could play an essential role in the management of ELBW infants with sBPD. Considering the limitations of a single center retrospective study, prospective randomized control trials are needed to confirm these findings.